Integrating Risk-Based Principles into Border Inspections and Clearance in Zambia - Nuamah, Peter (International Finance Corporation, Washington, DC, 2017)
Led by the Ministry of Commerce, Trade, and Industry, Zambia undertook a trade-facilitation needs assessment of its alignment with the articles of the World Trade Organization Trade Facilitation Agreement (WTO TFA) in January 2015. The assessment resulted in identification of gaps and recommendations for addressing them. This led to Zambia ratifying the WTO TFA on December 15, 2015. This smart lesson describes the process of setting up a plan for risk-based border inspections at the Zambia Bureau of Standards, and it shares some lessons learned.